Evaluasi Rasionalitas Peresepan Obat Berdasarkan Indikator World Health Organization (WHO) di Puskesmas “X” Yogyakarta - Yuni Andriani; Desinta Putri Kusuma; Nadia Husna (UNIVERSITAS MUHAMMADIYAH MATARAM, 2025)
Rational use of drugs is when patients get the right drugs with their clinical needs such as the right dose, right duration of administration, and the lowest cost of treatment. Based on the World Health Organization (WHO) report, more than 50% of drug prescribing in the world has not been rational, the impact includes unwanted side effects to bacterial resistance to antibiotics. Prescribing indicators according to the WHO can be used to evaluate the rational use of drugs. This study aims tofind out the rationality of prescribing drugs in Puskesmas based on WHO indicators. This study is an observational descriptive studywith a cross-sectional approach. The data used in this study were prescriptions for February, May and December 2022 which were collected retrospectively. The results of this study showed that most of the patients treated at Puskesmas